ANALISIS KETERAMPILAN PROSES SAINS SISWA PADA PEMBELAJARAN DARING - Norma Yunita; Tutut Nurita (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This research was conducted with the aim of analyzing students' science process skills in the online learning process at SMPN 58 Surabaya. The research method used in this research was descriptive survey with a quantitative approach. The subjects determination in this research were purposive sampling. Subjects in this research were 36 students of VIII grade at SMPN 58 Surabaya. The research instruments used were science process skills test sheets. Data collection techniques in this research were test. The test technique uses multiple choice questions. The data analysis technique used is descriptive statistical analysis. The results of students' science process skills such as student’s observing skills got 81.94% with high category, classifying skills got 69.44% with high category, predicting skills got 25.00% with low category, formulating skills’ problems got 37.50% with medium category, the skill to formulate hypotheses got 45.83% with medium category, the skill to determine the variable got 8.33% with the low category, investigating skills got 18.36% with the low category, data analysis skills got 16.67% with the low category, concluding skills got a percentage 18.05% with low category, communicating skills got 4.05% with the low category. The conclusion of this research was observing skills got the high category, and the lowest category was communicating skills.